Cryptococcosis - Zavala, Sofia; Baddley, John W. (Seminars in Respiratory and Critical Care Medicine, 2020)
Cryptococcosis has become an important infection in both immunocompromised and immunocompetent hosts. Although Cryptococcus is mainly recognized by its ability to cause meningoencephalitis, it can infect almost any organ of the human body, with pulmonary infection being the second most common disease manifestation. In cases of meningitis, symptom onset may be insidious, but headaches, fevers, or mental status changes should warrant diagnostic testing. Symptoms of pulmonary disease are nonspecific and may include fever, chills, cough, malaise, night sweats, dyspnea, weight loss, and hemoptysis. Due to protean manifestations of infection, diagnosis may be delayed or misdiagnosis may occur. Diagnosis typically is made by antigen testing of serum or cerebrospinal fluid or by culture or histopathology of infected tissues. A lumbar puncture with the measurement of opening pressure is recommended for patients with suspected or proven cryptococcosis. Treatment of cryptococcosis is based on the anatomical site of disease, severity of disease, and underlying immune status of the patient. Amphotericin B preparations plus 5-flucytosine is used as initial treatment of meningitis, disseminated infection, or moderate-to-severe pulmonary infection followed by fluconazole as a consolidation therapy. Fluconazole is effective for mild-to-moderate pulmonary infection. Important complications include elevated intracranial pressure and immune reconstitution syndrome, which may resemble active disease.
Keywords: Cryptococcus; Cryptococcus neoformans; Cryptococcus gattii; cryptococcosis; pneumonia; fluconazole; amphotericin B; flucytosine